Modelling and simulation of multiple-resistance conductive heat transfer phenomena - Chua, Kok Yong (2014)
An important aspect of chemical engineering curriculum is to teach one/multi-dimensional conduction, convection and radiation processes of heat transfer. To give better illustration of these concepts, a computer simulation tool is very important. This computer simulation tool acts as an additional teaching aid for visualizing the complex transport processes, and therefore is helpful in facilitating and enhancing learning development. The objective of this report is to develop mathematical programming of multiple-resistance conductive heat transfer phenomena using a mathematical software package, i.e., MATLAB. Mathematical software package can expose the students to theoretical and practical features of heat transfer. Furthermore, the definition of conduction is the transfer of energy through matter from particle to particle. It is a heat transfer directly through materials, occurring when mass of material stays in place. It is the transfer and delivery of heat energy from atom to atom within a substance. Conduction is most effective in solids but it can also happen in fluids. An experiment was conducted to measure the temperature along the surface of the pin fin assuming steady state heat transfer, free convection and the tip of the fin insulated. The experiment was repeated with different materials having different values of thermal heat conductivity (k) and a graph was plotted between temperature variance with length and time of the rod. The results obtain thought the simulation numerical coding and the experiments were verified by using the MATLAB Tool. Those data of results are obtaining through estimation and imagine via no experimental procedure evidence proof. Thus, a comparative study was done for each of the materials to see the temperature variation along the length and time of the rod in different cases